Pap Smear Performance Among Women in Basrah Cervical Screening - Elaf Zuhair Mansoor; Lamis Aziz Hameed; Hayat Yahya Al Mousaw (Academia Open, 2025)
General Background: Cervical cancer remains a leading cause of cancer-related mortality among women worldwide, particularly in developing countries where early detection programs are limited. Specific Background: The Papanicolaou (Pap) smear is a widely used, cost-effective screening method for detecting precancerous and cancerous cervical lesions. Despite its proven utility, misreporting and limited access continue to challenge accurate diagnosis in many regions. Knowledge Gap: There is limited data on the performance of Pap smear testing in Iraq, especially regarding sociodemographic factors influencing abnormal results. Aim: This study evaluates the performance of Pap smear tests among women attending the early detection cervical cancer screening center in Basrah and examines associations with sociodemographic characteristics. Methods & Results: A record-based cross-sectional study of 677 women from 2013–2015 showed 60.7% normal results, 18.8% LSIL, 4.3% HSIL, and 1–1.2% other abnormalities. Abnormal results were more prevalent in women aged 40 and above and were significantly associated with passive smoking, parity, and duration of marriage. Novelty & Implications: This study provides the first detailed insight into Pap smear performance in Basrah, highlighting population-specific risk factors that can guide targeted screening and early intervention strategies. Highlights: First evaluation of Pap smear performance in Basrah population. Abnormal results associated with age, parity, and passive smoking. Provides evidence for targeted cervical cancer screening programs. Keywords: Pap Smear, Cervical Cancer, Screening Performance, Basrah, Women Health